Quiet Contributors: The Role of the Arts, Humanities and Social Sciences in Innovation - Jonathan Linton (Foresight and STI Governance)
Many countries are directing their attention to the support of technological innovation with the intent to obtain economic and social benefits at home while positioning themselves for high margin, high technology export markets. The under-considered and under-exploited role of arts, humanities and social science in innovation is explored in this study. Examples of programs and activities in a variety of countries are illustrated. Insight into why the arts, humanities and social sciences are important to the generation of social and economic benefits through innovation is  offered. Furthermore, recommendations are provided for better accessing the benefits that the arts, humanities and social science can provide.